The New Tijāni Mahdī and Contested Authenticity: The El Cheikh Phenomenon in Contemporary Senegal - Lo, Cheikh Tidiane (Journal of religion in Africa, 2026)
This paper aims to examine the social and religious context of a new Mahdī’s rise in Senegal, his supposed proofs, and the counter-narratives that challenge the authenticity of his title as well as the communicative resources mobilized in support of and against the mission. The paper first offers a short biography of the new Mahdī named El Cheikh, and his rise to mahdīyya. Before analyzing his supporting arguments and strategies to win recognition and consolidate his legitimacy, a conceptual framework of Mahdism and what Max Weber terms charismatic leadership is presented as a template to structure the study. The rest of the paper studies the contesting voices of some Muslim authorities and preachers, especially among the Tijani community, highlighting the grounds on which they challenge and delegitimize the new Mahdī. It is argued that the emergence of this charismatic religious figure in a context of economic vulnerability and crisis of authority is likely to succeed, at least as a crystallized religious community of his followers, because of the sense of spiritual, psychological, and economic favors it promises to an increasing number of desperate youth in a quest for a more secure future.